Relative Salt Tolerance of Different Varieties of Barley (Hordeum Vulgare L.) at Germination and Seedling Stage - Rathore, A K; Sharma, R K; Lal, P (Annals of Arid Zone, 2016)
An experiment was conducted to study the effect of different levels of salinity (0, 24, 32 and 40 mmhos/cm) on germination of the seeds of 22 varieties of Barley (Hordeum vulgare L.). Germination was delayed and the percentage of germination decreased with an increase in salinity levels. The varieties ’Mexican 19’, ’Russian 20’, ’Jyoti’, ’Belodi 16’, ’N.P. 21’, ’BHD 44’, and ’RSD 29’ germinated satisfactorily upto the EC level of 32 mmhos/cm. Only two varieties i.e. ’Jyoti’ and ’Russian 20’ had more than 50 per cent germination (67.7 and 52.5 per cent respectively) at the salinity level of 40 mmhos/cm. ’RDB 1’, ’RMB 9’, ’RS 6’, ’C 138’, ’RS 55’, ’RD 31’, ’Mexican 22’, and ’BL 41’ could germinate satisfactorily only at EC level of 24 mmhos/cm. ’BG I’, ’HD 37’, ’K 15/96-1’, ’RD 57’, ’RD 118’, ’DG 2’ and ’DL 26’ had the least relative salt tolerance of all the varieties.